2020
DOI: 10.1111/1751-2980.12837
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with disability in patients with ulcerative colitis: A cross‐sectional study

Abstract: Objectives Ulcerative colitis (UC) can give rise to several restrictions of patients' working and social activities. We aimed to determine the association between disease chronicity and the state of disability in a large population with UC. Methods We recruited consecutive patients with UC attending the inflammatory bowel disease (IBD) unit of the Azienda Ospedaliera of Padua between July and December 2017. We collected patients' characteristics and clinical information, and all participants completed the IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…36 In addition, several studies have shown that the disabilities of UC patients, which closely affects the quality of life, worsened as the disease activity index increased. [37][38][39] We also found correlations between inflammatory markers (CRP, ESR, and white blood cell count) and HRQL. As far as we know, there are few studies that have attempted to directly correlate laboratory findings and HRQL results.…”
Section: Discussionsupporting
confidence: 56%
“…36 In addition, several studies have shown that the disabilities of UC patients, which closely affects the quality of life, worsened as the disease activity index increased. [37][38][39] We also found correlations between inflammatory markers (CRP, ESR, and white blood cell count) and HRQL. As far as we know, there are few studies that have attempted to directly correlate laboratory findings and HRQL results.…”
Section: Discussionsupporting
confidence: 56%
“…Accordingly, a systematic literature review concluded that treatments which induce and maintain remission reestablish both physical and mental health status [37] . Indeed, a recent cross-sectional study [38] . Work overload has also been perceived as the cause of the disease more frequently in active patients compared to patients in remission [23] .…”
Section: The Importance Of Treatment In Restoring Quality Of Lifementioning
confidence: 99%
“…Inflammatory Bowel Diseases (IBDs), including Ulcerative Colitis (UC) and Crohn’s Disease (CD), are chronic disorders of the intestinal tract characterized by relapsing and remitting intestinal inflammation and are associated with a reduced quality of life. 1 6 The introduction of biological drugs has radically changed the therapeutic approach and management of IBD patients. 1 …”
Section: Introductionmentioning
confidence: 99%